THE EFFECT OF FINANCIAL RATIOS ON SHARE PRICE CONSUMER GOODS SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Wulandari, Siska (Journal of Research in Business, Economics, and Education, 2020)
Increased consumption is a positive driving force for manufacturing companies especially those engaged in the field of consumer goods. No exception on stock trading, Consumer Goods index posted the highest growth compared with the other sectoral indices. In the investment decision, shareholders using financial ratios as a reference in selecting companies to invest. The ratio used in this study is the Net Profit Margin (NPM), Earning Per Share (EPS) and Dividend Per Share (DPS) .This research is a quantitative research methods and panel data regression analysis using software Eviews 10. The data used is data secondary form of annual data obtained from the Indonesia Stock Exchange, Indonesian Central Securities Depository and the company's official website, with technical documentation. The sampling technique was conducted using purposive sampling and got 44 data during the period from 2015 to 2018 in 11 companies manufacturing consumer goods sector listed on the Stock Exchange Indonesia.Hasil testing using the t test to the conclusion that the variable Net Profit Margin and Earning Per Share has no effect on stock prices, whereas only Per Share Dividend variables that have a positive and significant effect on stock prices of companies manufacturing consumer goods sector listed in Indonesia stock Exchange during the study period.